The effectiveness of self-compassion on the sleep quality and life quality of mothers with children with attention-deficit/hyperactivity disorder - Sevda Mohammadi; Roghayeh Kiyani (Social Determinants of Health)
Background: This study aimed to investigate how self-compassion affected the quality of sleep and overall well-being of moms whose children had been diagnosed with ADHD (Attention Deficit Hyperactivity Disorder).